Expression of Gastrin-Releasing Peptide Receptor in Breast Cancer and Its Association with Pathologic, Biologic, and Clinical Parameters: A Study of 1,432 Primary Tumors - Morgat, Clément; MacGrogan, Gaétan; Brouste, Véronique; Vélasco, Valérie; Sévenet, Nicolas; Bonnefoi, Hervé; Fernandez, Philippe; Debled, Marc; Hindié, Elif (The Journal of nuclear medicine (1978), 2017)
A growing body of evidence suggests that gastrin-releasing peptide receptor (GRPR) might be a valuable target in breast cancer. To understand which patients can be potential candidates for GRPR-based imaging or targeted therapy, we screened invasive breast cancers by immunohistochemistry for the presence and intensity of GRPR expression. We explored a tissue microarray of 1,432 primary breast tumors from patients who underwent surgery between 2000 and 2005 at Institut Bergonié, without prior neoadjuvant treatment. We studied associations between GRPR expression and clinical, pathologic, and biologic parameters. The association between GRPR expression and distant metastasis-free interval was also examined. GRPR overexpression was found in 75.8% of the 1,432 tumors and was most strongly associated with estrogen receptor (ER) positivity (GRPR was high in 83.2% of ER-positive and 12% of ER-negative tumors; < 0.00001). When molecular subtypes of breast cancer were considered, GRPR was overexpressed in 86.2% of luminal A-like tumors, 70.5% of luminal B-like human epidermal growth factor receptor 2 (HER2)-negative tumors, 82.8% of luminal B-like HER2-positive tumors, 21.3% of HER2-enriched tumors, and 7.8% of triple-negative tumors. Importantly, when breast tumors overexpressed GRPR, high GRPR expression was also found in metastatic lymph nodes in 94.6% of cases. Primary tumors with high GRPR expression were associated with lower risk of distant metastases at follow-up in univariate analysis (Log-rank = 0.0084) but not in multivariate analysis. Hence, the prognostic impact of GRPR was lost when examined within specific molecular subtypes. Because GRPR is overexpressed in a high percentage of ER-positive tumors, GRPR targeting offers wide perspectives for imaging and treatment in patients with ER-positive breast cancer, using recently developed radiolabeled GRPR ligands.